2018
DOI: 10.1097/gme.0000000000001279
|View full text |Cite
|
Sign up to set email alerts
|

Can the use of probiotics in association with isoflavone improve the symptoms of genitourinary syndrome of menopause? Results from a randomized controlled trial

Abstract: Objective: To evaluate the effect of isoflavone administration, either in conjunction with probiotic use or not, on the symptoms of genitourinary syndrome of menopause, and compare the effects with those of hormone therapy. Methods: A randomized clinical trial was conducted on 60 postmenopausal women aged 40 to 60 years, randomly assigned to receive oral isoflavone (150 mg dry extract of glycine max) alone or isoflavone plus probiotic (Lactobacillus aci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(28 citation statements)
references
References 39 publications
0
25
0
Order By: Relevance
“…Recently, a randomized clinical trial was conducted on 60 postmenopausal women, who were randomly assigned to receive oral isoflavone (150 mg dry extract of glycine max) alone or isoflavone plus probiotic or hormone therapy (1 mg estradiol and 0.5 mg norethisterone acetate) to evaluate genitourinary symptoms and vaginal atrophy [50]. The result revealed that after 16 weeks of treatment, the urogenital symptoms including vaginal dryness and complaints of sexual problem as well as the maturation value, vaginal pH and vaginal flora improved significantly in the hormone therapy group.…”
Section: Female Urogenital Systemmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, a randomized clinical trial was conducted on 60 postmenopausal women, who were randomly assigned to receive oral isoflavone (150 mg dry extract of glycine max) alone or isoflavone plus probiotic or hormone therapy (1 mg estradiol and 0.5 mg norethisterone acetate) to evaluate genitourinary symptoms and vaginal atrophy [50]. The result revealed that after 16 weeks of treatment, the urogenital symptoms including vaginal dryness and complaints of sexual problem as well as the maturation value, vaginal pH and vaginal flora improved significantly in the hormone therapy group.…”
Section: Female Urogenital Systemmentioning
confidence: 99%
“…Therefore, it was concluded that probiotics improved the metabolism of isoflavones after 16 weeks of treatment. However, the increase in the contents of isoflavones and their metabolites failed to yield an estrogenic effect on the urogenital tract and relieve vulvovaginal symptoms [50].…”
Section: Female Urogenital Systemmentioning
confidence: 99%
“…Taking this into consideration, it has been suggested to combine soy isoflavones with lactic acid bacteria in the form of spores, resistant to the gastric and biliary secretion, to assure the bioavailability of soy isoflavones [67,68]. The association with probiotic was also studied for symptoms of genitourinary syndrome of menopause, but results were not satisfactory [69]. Isoflavones exert a limited beneficial effect on cognition, as increased choline acetyltransferase and brain-derived neurotrophic factor in the hippocampus and frontal cortex [70].…”
Section: Phytoestrogensmentioning
confidence: 99%
“…A clinical trial on 60 postmenopausal women (aged 40 to 60 years), randomly assigned to receive oral isoflavone (150 mg dry extract of glycine max) alone, or isoflavone plus probiotic (L. acidophilus, L. casei, Lactococcus lactis, Bifidobacterium bifidum, and Bifidobacterium lactis), or hormonal therapy (1 mg estradiol and 0.5 mg norethisterone acetate) has demonstrated that after 16 weeks the hormonal therapy group showed an increased number of lactobacilli in the vagina, similar to that seen in premenopausal state, and a decrease vaginal PH; conversely no change in pH value was found in the isoflavone group and isoflavone plus probiotic group (Ribeiro et al, 2018). A recent study by Cohen et al (2020) conducted on 228 premenopausal suggested that daily administration of vaginal dose of Lactobacillus crispatus,after treatment with vaginal metronidazole, can reduce recurrence of bacterial vaginosis after 12 weeks.…”
Section: Menopausementioning
confidence: 99%